Physical-constraint-guided semi-supervised learning for tile hollow area visualization - Keyan Ji; Linyuan Ma; Qingzhao Kong (Engineering Structures, 2026)

Fine-grained hierarchical crop type classification from integrated hyperspectral EnMAP data and multispectral sentinel-2 time series: A large-scale dataset and dual-stream transformer method - Wenyuan Li; Shunlin Liang; Yuxiang Zhang; Liqin Liu; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Shikang Guan; Zhenwei Shi (Remote Sensing of Environment, 2026)

Agglomeration under strain: Nonlinear dynamics of urban functional conflicts - Hongbo Zhao; Zeting Jia; Wenhui Yue; Yansui Liu; Qiyang Liu; Li Yue; Shaozhen Cao; Yilin Ma; Keyan Lu (Sustainable Cities and Society, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

AgriFM: A multi-source temporal remote sensing foundation model for Agriculture mapping - Wenyuan Li; Shunlin Liang; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Yuxiang Zhang; Shikang Guan; Husheng Fang; Zhenwei Shi (Remote Sensing of Environment, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

MnFe2O4 coupled with MgAl-LDH for activation of periodate towards enhanced degradation of organic pollutants in water - Ya Sun; Chang Ma; Yawei Shi; Zonglin Pan; Yumei Xing; Yan Wang; Keyan Liu; Guanghui Ding (Journal of Water Process Engineering, 2025)

Quantitative Risk Assessment of Wellbore Collapse of Inclined Wells in Formations with Anisotropic Rock Strengths - Tianshou Ma; Keyan Liu; Yi Qiu; Jinhua Liu; Dmitriy A. Martyushev; P. G. Ranjith (Rock Mechanics and Rock Engineering, 2025)

Insights into the differences in meat quality among different sheep breeds in the Qilian Mountains from the perspective of metabolomics and transcriptomics - Keyan Ma; Juanjuan Song; Dengpan Li; Zilong Liu; Chunhui Wang; Taotao Li; Youji Ma (Food Bioscience, 2025)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Investigation on the anisotropy of meso-mechanical properties of shale rock using micro-indentation - Tianshou Ma; Keyan Liu; Xue Su; Ping Chen; P. G. Ranjith; Dmitriy A. Martyushev (Bulletin of Engineering Geology and the Environment, 2024)

Thiol “click” chromene mediated cascade reaction forming coumarin for in-situ imaging of thiol flux in drug-induced liver injury - Yutao Yang; Keyan Zhou; Ming Ma; Hongmei Liu; Ming Jin; Caixia Yin; Shuxiang Wang; Jinchao Zhang (Chemical Engineering Journal, 2023)

Overestimated gains in water‐use efficiency by global forests - Xiao Ying Gong; Wei Ting Ma; Yong Zhi Yu; Keyan Fang; Yusheng Yang; Guillaume Tcherkez; Mark A. Adams (Global Change Biology, 2022)
Increases in terrestrial water‐use efficiency (WUE) have been reported in many studies, pointing to potential changes in physiological forcing of global carbon and hydrological cycles. However, gains in WUE are of uncertain magnitude over longer (i.e. >10 years) periods of time largely owing to difficulties in accounting for structural and physiological acclimation. 13 C signatures (i.e. δ 13 C) of plant organic matter have long been used to estimate WUE at temporal scales ranging from days to centuries. Mesophyll conductance is a key uncertainty in estimated WUE owing to its influence on diffusion of CO 2 to sites of carboxylation. Here we apply new knowledge of mesophyll conductance to 464 δ 13 C chronologies in tree‐rings of 143 species spanning global biomes. Adjusted for mesophyll conductance, gains in WUE during the 20th century (0.15 ppm year −1 ) were considerably smaller than those estimated from conventional modelling (0.26 ppm year −1 ). Across the globe, mean sensitivity of WUE to atmospheric CO 2 was 0.15 ppm ppm −1 . Ratios of internal‐to‐atmospheric CO 2 (on a mole fraction basis; c i / c a ) in leaves were mostly constant over time but differed among biomes and plant taxa—highlighting the significance of both plant structure and physiology. Together with synchronized responses in stomatal and mesophyll conductance, our results suggest that ratios of chloroplastic‐to‐atmospheric CO 2 ( c c / c a ) are constrained over time. We conclude that forest WUE may have not increased as much as previously suggested and that projections of future climate forcing via CO 2 fertilization may need to be adjusted accordingly.

The intra-annual intrinsic water use efficiency dynamics based on an improved model - Xiaojin Bing; Keyan Fang; Xiaoying Gong; Wenzhi Wang; Chenxi Xu; Maihe Li; Chaoyue Ruan; Weiting Ma; Yingjun Li; Feifei Zhou (Climatic Change, 2022)